Palliative pelvic exenteration: A systematic review of patient-centered outcomes. Issue 10 (October 2019) - ; Kroon, Hidde M.; Dudi-Venkata, N.N.; Bedrikovetski, S.; Thomas, M.L.; Kelly, M.E.; Aalbers, A.G.J.; Abdul Aziz, N.; Abraham-Nordling, M.; Akiyoshi, T.; Alberda, W.; Andric, M.; et al.
Abstract: Objective: Palliative pelvic exenteration (PPE) is a technically complex operation with high morbidity and mortality rates, considered in patients with limited life expectancy. There is little evidence to guide practice. We performed a systematic review to evaluate the impact of PPE on symptom relief and quality of life (QoL). Methods: A systematic review was conducted according to the PRISMA guidelines using Ovid MEDLINE, EMBASe, and PubMed databases for studies reporting on outcomes of PPE for symptom relief or QoL. Descriptive statistics were used on pooled patient cohorts. Results: Twenty-three historical cohorts and case series were included, comprising 509 patients. No comparative studies were found. Most malignancies were of colorectal, gynaecological and urological origin. Common indications for PPE were pain, symptomatic fistula, bleeding, malodour, obstruction and pelvic sepsis. The pooled median postoperative morbidity rate was 53.6% (13–100%), the median in-hospital mortality was 6.3% (0–66.7%), and median OS was 14 months (4–40 months). Some symptom relief was reported in a median of 79% (50–100%) of the patients, although the magnitude of effect was poorly measured. Data for QoL measures were inconclusive. Five studies discouraged performing PPE in any patient, while 18 studies concluded that the procedure can be considered in highly selected patients. Conclusion: Available evidence on PPE is of low-quality. Morbidity and mortality rates are high with a short median OS interval. While some symptom relief may be afforded by this procedure, evidence for improvement in QoL is limited. A highly selective individualised approach is required to optimise the risk:benefit equation.